Menguatkan Citra Destinasi; Pengalaman Pengunjung, Fasilitas Wisata Terhadap Loyalitas Pengunjung yang di Mediasi oleh Citra Destinasi - Ely, Sugiarto; Asnawi , Aisah; Pelupessy, Merry Margareth (KAMBOTI: Jurnal Sosial dan Humaniora, 2024)
This research aims to understand the influence of Visitor Experience and tourism Facilities on Visitor Loyalty through Destination Image as a mediating variable. This type of research is quantitative. The type of data in this research is quantitative and the data source uses primary data. The population in this study were Maluku people who visited the Air Putri tourist attraction more than twice and the number of samples in this study was 174 people. The sampling method used was non-probability sampling. The data analysis method uses Partial Least Square (PLS) and the data is processed using the SmartPlS software version 4.1.0.6. The research results show that Visitor Experience has a positive but not significant effect on Visitor Loyalty, Visitor Experience has a positive and significant effect on Destination Image, Tourist Facilities have a positive and significant effect on Destination Image, Tourist Facilities have a positive and significant effect on Visitor Loyalty, Destination Image has a positive and significant to Visitor Loyalty, Visitor Experience has a positive and significant effect on Visitor Loyalty through the mediation of Destination Image, Tourist Facilities are positive and significant to Visitor Loyalty through the mediation of Destination Image.